Analisa Pengaruh Volume Tabung Udara terhadap Debit Air yang Dihasilkan pada Perancangan Pompa Hydram - Ayu Pitri Yeni; Yuli Yetri; Ilham Handoko; Asmed Asmed; Menhendry Menhendry; Bukhari S (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Currently, the technology for supplying water is still mostly using pumps with electric motor drives. Most of these pumps are dependent on electrical energy or fuel oil as the pump driving energy. One of the technologies being developed is the hydraulic ram pump. The hydraulic ram works on the water hammer principle. When the fluid flow is stopped suddenly, the change in momentum of the fluid mass will increase the pressure suddenly. This increased pressure is used to lift some of the water to higher ground. So a hydraulic ram pump is designed that uses the potential energy of water as its driving force. In designing the hydraulic ram pump that the author did, using a variation of the height of the air tube with a height of 100 cm, 80 cm and 60 cm with a diameter of 3 inches and an outlet pipe diameter of inch with a water source height of 0.5 m. From the experiment, the maximum pump discharge was obtained on an air tube with a height of 100 cm with a discharge of 0.010309 L/s.